Intergenerational Fairness During Demographic Transition - Matthias Heidler; Jasmin Häcker (Albert-Ludwigs-Universität Freiburg, Institut für Finanzwissenschaft, 2004)
Implementing a fairness component into a standard overlapping-generations model and allowing young individuals to vote on their own pension payments, we show that they adapt the pay-as-you-go pension scheme to future demographic changes. In particular, we explain why young generations cut their retirement benefits thus partially phasing out social security during a fertility decline. Carrying out a simulation, we furthermore calculate the costs of implementing fairness into utility. From the viewpoint of an individual, these costs are reduced by equalizing generational accounts. Hence, under certain conditions policy actions based on generational accounts may be compatible with intertemporal welfare maximization.
urn:nbn:de:bsz:25-opus-18548
Keywords: D63; H55; 330; intergenerational fairness; social security; demography; Generationenbeziehungen; Gerechtigkeit; Soziale Sicherung; Overlapping Generations; Public Choice; Umlageverfahren; Intergenerative Belastungsrechnung; Zeitpräferenz; Alternde Bevölkerung; Theorie